Airlangga Pribadi Kusman’s the vortex of power intellectuals and politics in Indonesia’s post-authoritarian era - Sahrasad, Herdi (Humanities Diliman, 2021)
Available online: https://journals.upd.edu.ph/index.php/humanitiesdiliman/article/view/7731/6739